The Impact of Financial Malpractice on Service Delivery: A Conceptual Examination of Literature - Baloyi, Wiston Mbhazima; Erasmus Beyers, Lourens Johannes (Asian Journal of Social Sciences and Management Studies, 2019)
This paper argues that financial malpractice has not always been remedied in the public sector. Legislation that governs financial administration in the public sector is, thus, being disregarded. Officials continuously engage in unwanted expenditure (i.e. unauthorised, irregular, fruitless and wasteful expenditure) and no action is taken against them. The purpose of this paper was to probe the impact of financial malpractice by public officials as an impediment to service delivery. The methodological approach of this paper was the conceptual examination of literature which ultimately lead to proposed strategy measures towards financial malpractice and service delivery. This paper finds that officials unethically pursue their self-interest in enriching themselves by looting the government funds and neglecting the focus of enhancing service delivery. Consequently, this has relegated the impoverished citizens to a crisis situation. The lack of proper planning and the embezzlement of public funds have both been identified as factors that impede service delivery. This paper suggests that the government should tighten its internal control measures and reinforce compliance with the applicable laws and regulations. Furthermore, it suggests that officials should be held liable for any financial malpractice and, therefore, penalties for financial misconduct should be instituted against them. Lastly, government should provide comprehensive training and awareness programmes on financial malpractice and financial misconduct.